System wide MV distribution network technical losses estimation based on reference feeder and energy flow model - Ibrahim K.A.; Au M.T.; Gan C.K.; Tang J.H. (Elsevier Ltd, 2023)
Electric losses; Electric power utilization; Energy dissipation; Feeding; Analytical equations; Energy flow modeling; Estimation approaches; Integrated analytical approaches; Load distributions; Medium-voltage distribution networks; MV distribution networks; Reference network; Electric power distribution